A survey on perceptions of piano teaching materials of ABRSM implementers and non-ABRSM implementers - Diaz, James C.
This study aims to compare the teaching materials used by ABRSM implementers based from the ABRSM piano syllabi in 2008 with the teaching materials used by non-ABRSM implementers with regard to its practicability.